Development of a Clinical Practice Guideline for Lower Limb Amputees. A Knowledge Translation Process in a Middle Income Country - Posada-Borrero, Ana Maria; Patiño-Lugo, Daniel Felipe; Plata-Contreras, Jesus Alberto; Velasquez-Correa, Juan Carlos; Lugo-Agudelo, Luz Helena (Frontiers in Rehabilitation Sciences, 2022)
Background: Knowledge translation processes are necessary for improving patients’ and communities’ health outcomes. The aim of this study was to systematically develop evidence-based recommendations for people over 16 years of age who are in risk for or have suffered a lower limb amputation for medical reasons or trauma in order to improve function, quality of life, decrease complications and morbidity. Methods: Following the Grading of Recommendations Assessment, Development and Evaluation (GRADE) approach we developed a Clinical Practice Guideline (CPG) for lower limb amputees with funding from the Ministry of Health in Colombia and participation of a multidisciplinary group. We included patients’ preferences. Based on the scope, purposes and objectives the questions were elaborated with the PECOT strategy. The evidence search was performed for each question in the main databases: Cochrane Library, Embase and PubMed, without time or language restriction. Teams were formed with thematic experts and clinical epidemiologists to review the clinical studies, describe the evidence, and evaluate the quality of the body of evidence with the GRADE methodology. The recommendations were made according to the judgments proposed by the GRADE working group. We conducted a stakeholder´s dialogue as a mechanism for the external validation of the guideline implementation. Results: The CPG included 43 recommendations related to the diagnosis, surgical treatment, rehabilitation, prescription and adaptation of the prosthesis. They were strong in favor 37.2%, weak in favor 53.5%, strong against 2.3%, Weak against 7.0%. Quality of evidence was high in 0%, moderate in 11.6%, low in 58.1% and very low in 30.2%. Discussion: In 93% of the recommendations, the quality of the evidence was between low and very low. This is why it was so important to validate and discuss each recommendation with an expanded multidisciplinary group. The research group identified 25 interventions and five milestones to be prioritized in the implementation and in the stakeholder´s dialogue participants identified opportunities and barriers for implementation of recommendations. Conclusion: It is necessary to develop a national policy for implementation strategies of CPG recommendations that promotes the necessary arrangements for the provision of services for diagnosis, treatment, and rehabilitation of lower limb amputees.